Fatty acid and tocochromanol patterns of Turkish Pinus L. (Pinaceae) - Karaagach, EBY; Brauehl, L (Bangladesh Botanical Soc, 2004)
Pinus of family Pinaceae is known to contain a set of unusual fatty acids in the seed oils. In Turkey the fatty acid and tocochromanols (tocopherols and tocotrienols) composition of the seed oils, was less studied particularly in view of chemotaxonomy. In this study, the fatty acid, tocopherol, tocotrienol and plastochromanol-8 contents of Pinus L. taxa naturally growing in Turkey (P. nigra subsp. pallasiana, P. nigra subsp. pallasiana var. pyramidata, P. halepensis, P. sylvestris, P. pinea, P. brutia, P. radiata and P. pinaster) were determined. The relative concentrations of the fatty acids (oleic, linoleic, alpha-linolenic-taxolenic, pinolenic and coniferonic acid) and also the tocochromanol contents in species of Pinus seed oils are suggested to have chemotaxonomic value. The amount of the unsaturated fatty acid (USFA) comprises 90% of the seed oil. While gamma-tocopherol was found as the highest component in all of the Pinus seed oil. beta tocotrienol was not found in any of them. Total tocopherol amount of studied taxa was found very high than the tocotrienols. In particular, the presence of unsaturated polyethylene-interrupted fatty acids (Delta5-UPIFA) such as, taxoleic and pinolenic acids are determined and marked as indicators of phylogenetic relationship.
Keywords: Pinus; chemotaxonomy; GC; fatty acid fingerprints; tocochromanols